Kant, Herder, and the birth of anthropology - Zammito, John H. (University of Chicago Press, 2002)
If Kant had never made the critical turn of 1773, would he be worth more than a paragraph in the history of philosophy? Most scholars think not. But in this pioneering book, John H. Zammito challenges that view by revealing a precritical Kant who was immensely more influential than the one philosophers think they know. Zammito also reveals Kant's former student and latter-day rival, Johann Herder, to be a much more philosophically interesting thinker than is usually assumed and, in many important respects, historically as influential as Kant. Relying on previously unexamined sources, Zammito traces Kant's friendship with Herder as well as the personal tensions that destroyed their relationship. From this he shows how two very different philosophers emerged from the same beginnings and how, because of Herder's reformulation of Kant, anthropology was born out of philosophy.